Correction: Conversion of N-acyl amidines to amidoximes: a convenient synthetic approach to molnupiravir (EIDD-2801) from ribose. Issue 17 (4th April 2022) - Ahmed, Ajaz; Ahmed, Qazi Naveed; Mukherjee, Debaraj
Abstract : Correction for 'Conversion of N -acyl amidines to amidoximes: a convenient synthetic approach to molnupiravir (EIDD-2801) from ribose' by Ajaz Ahmed et al., RSC Adv., 2021, 11, 36143–36147, DOI: ; 10.1039/D1RA06912H .